Kebijakan Sertifikasi Halal Sebagai Upaya Peningkatan Akses Pasar UMKM Pangan Di Kota Dumai - Desinta Bella Irwana; Sindi Rahayu; Erinaldi Erinaldi (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study seeks to examine how halal certification policies are implemented as a strategy to expand market access for food-based MSMEs in Dumai City. Using a literature review within a qualitative descriptive framework, the research explores the regulatory foundation, the Free Halal Certification Program (SEHATI), and the respective roles of BPJPH, local government, and MUI. Findings indicate that halal certification functions not only as a form of religious assurance but also as an economic tool that increases consumer confidence, widens the halal product market, and strengthens the competitiveness of local MSMEs. The SEHATI initiative in Dumai has effectively boosted business participation and raised public understanding regarding the significance of halal labeling. It has also contributed to turnover growth of up to 45%, empowered women-led enterprises, and reinforced Dumai’s positioning as a leading halal culinary destination. Despite these achievements, challenges remain, including a limited number of halal facilitators, inadequate digital literacy among business operators, and insufficient coordination across involved institutions.